24 February, 13:45
5 (4z+6) - 2 (z-4) = 2 (2w^2+7w-3)
24 February, 14:33
If you are solving for "z", the answer is
z=2w^2+7w/10 - 2
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅
“5 (4z+6) - 2 (z-4) = 2 (2w^2+7w-3) ...”
in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers
New Questions in Mathematics
Graph. f (x) = |2x-6|+3
If X = (8,4) and Y = (-8, 0), what is XY? А. 16.49 В. 2 С. 272 D. 8.94
You can walk 1/2 miles in half an hour what is your average speed
To generate an angle with a measure of 45°, there must be a clockwise direction of rotation. true or false
the martin want to buy a new computer. the regular price is $632. the store is offering a 25% discount and a sales tax of 7% is added after the discount. what is the total cost of the computer?
» 5 (4z+6) - 2 (z-4) = 2 (2w^2+7w-3)